EFEKTIVITAS PENYELENGGARAAN SISTEM LAYANAN DAN RUJUKAN TERPADU (SLRT) OLEH DINAS SOSIAL DALAM PENANGANAN KEMISKINAN DI KOTA BEKASI - Ahmad Lauhil Mahfudz; Siti Nuraini (Governance, 2022)
This study aims to analyze and identify the effectiveness of the implementation of the Integrated Service and Referral System (SLRT) in Poverty Management in Bekasi City. The method used in this study is a descriptive method with a qualitative approach. Data collection techniques with primary data collection in the form of interviews and observations in the field, and secondary data collection in the form of documentation. Determination of informants in this study was done by purposive sampling technique. Where the informants in this study consisted of Plt. Mayor of Bekasi, Head of Social Service of Bekasi City, Secretary of Social Service of Bekasi City, Head of Social Empowerment Division, Member of Commission IV of Bekasi City DPRD and the Community. The data obtained is then analyzed qualitatively by reviewing all the data collected which is supported by the results of interviews with the theoretical approach proposed by Budiani that to determine the measure of the effectiveness of a program can be seen from four indicators, namely the determination of program targets, program socialization, achievement of program goals and monitoring. Program.From the research results, it can be seen that the effectiveness of the implementation of the Integrated Service and Referral System (SLRT) by the Social Service in handling poverty in Bekasi City is quite effective and on target. This is based on the Integrated Social Welfare Data (DTKS) for 2020-2021, which shows that the number of poor people in Bekasi City has decreased by 0.3%.